THE RELATIONSHIP BETWEEN THE QUALITY OF EARNINGS AND VOLUNTARY DISCLOSURE - Mohammed Awad Abdullah; Prof. Dr. Muthana Rokan (Scholar Express Journals, 2022)
In this study, the results of the statistical analysis and hypothesis testing were extracted. It was found through the results of the hypothesis testing that there is a positive (direct) correlation with a significant significance between the quality of earning with optional disclosure in the two dimensions of non-financial measures and expected information.
Keywords: profit quality; voluntary disclosure; profit continuity